2022
DOI: 10.1016/j.toxrep.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam as an inadvertent anti-aphrodisiac in male bees

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Additionally, we found bumble bee males to be significantly more sensitive than workers and queens. As pesticides may impact the mating success and fertility of bumble bee males 53 , their exposure might have negative impacts on population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found bumble bee males to be significantly more sensitive than workers and queens. As pesticides may impact the mating success and fertility of bumble bee males 53 , their exposure might have negative impacts on population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on chemical communication and precopulatory behavior being estimators of reproductive output and on the evidence of bee population decline in agricultural environments (Sandrock et al, 2014;Rundlöf et al, 2015;Woodcock et al, 2017;Stuligross & Williams, 2020;Willis Chan & Raine, 2021), we need to acknowledge the genuine concerns being raised that effects on mating behavior lead to reductions in bee populations. Although our overall knowledge of the impact of pesticides on mating is limited at present, it is supported for at least three major crop pollinators with differing sociality levels: (1) eusocial honey bees, Apis mellifera (McAfee et al, 2022), (2) primitively eusocial bees, Bombus terrestris (Straub et al, 2022), and (3) the solitary bee Osmia cornuta (Boff et al, 2022), in addition to the oligolectic bee H. truncorum (this study).…”
Section: Impacts Of Pesticides On Precopulatory Behaviormentioning
confidence: 78%
“…Sublethal effects of pesticides have been found to interfere in courtship and consequently in mating in bees (Boff et al, 2022;McAfee et al, 2022;Straub et al, 2022), providing an additional mechanism explaining wild bee decline in agricultural environments (Rundlöf et al, 2015;Woodcock et al, 2017;Willis Chan & Raine, 2021). Despite evidence of these impacts, only a few studies have demonstrated the mechanism in which pesticides affect mating behavior in wild bees (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Zhang et al, 2019c;Tu and Chen, 2021). However, several studies indicate that NEOs may cause harm to non-target organisms, such as butter ies (Knight et al, 2021), bees (Anderson and Harmon-Threatt, 2021;Straub et al, 2022), zebra sh (Guerra et al, 2021), and Daphnia magna (Farkas et al, 2022). In addition, NEOs have been reported to harm the neurological (Costas-Ferreira and Faro, 2021), reproductive (Zhao et al, 2021), and hepatic (Abou-Zeid et al, 2021) functions of mammals.…”
Section: Introductionmentioning
confidence: 99%